Sex partner behavior variation related to network position of and residential proximity to sex partners among young black men who have sex with men - Chen, Yen-Tyng (AIDS Behav, 2020)
This analysis examines how sex behaviors are influenced by a sex partner’s network bridging position and the residential proximity between the two. The study sample consisted of 437 young black men who have sex with men (YBMSM) in Chicago and their sex partners (2013-2014). Dyadic analyses that clustered on individuals using generalized estimating equations (n=1095 relationships) were conducted to assess the associations between different HIV-related sexual behaviors and the network position of and residential proximity to a partner. The odds of group sex was higher with partners who had high network bridging, regardless of how close they lived to one another. The odds of transactional sex was higher with partners who had high network bridging and lived in a different region of the city. Sex behaviors associated with an increased risk of HIV transmission were associated with the network structural position of and residential proximity to partners among YBMSM.